Effect of Soybean Oil and Fish Oil on Lipid-Related Transcripts in Subcutaneous Adipose Tissue of Dairy Cows - Einar Vargas-Bello-Pérez (Animals, 2019)
The objective of this study was to determine the effect of long-term supplementation of unsaturated oil on lipid metabolism and transcription of genes involved in lipid metabolism in subcutaneous adipose tissue (SAT) of mid-lactating dairy cows. The objective was achieved by supplementing dairy cows with soybean oil (SO; high in linoleic acid) or fish oil (FO; high in EPA and DHA) for 63 days (nine weeks). Cows were fed a control diet with no added lipid, or diets containing SO or FO (n = 5 cows/group). At the onset of the experiment (day 0) and on days 21, 42, and 63 of supplementation, blood and SAT samples were collected from each animal. Oil supplementation increased cholesterol and NEFA in plasma, with a greater effect of SO compared to FO. Concentration of BUN was lower in SO compared to control and FO at the end of the trial. Transcription of few genes was affected by dietary lipids: FABP4 had lowest expression in FO followed by SO and control. ACACA and FASN had higher expression in FO. Transcription of SCAP was higher but expression of INSIG1 was lower in SO. Overall, results revealed that compared to control, SO and FO had lipogenic effect in SAT.